Rare Pulmonary Tumors and Carcinoma Mimickers; Experience from an Interventional Radiology Unit with Radiologic-pathologic Correlation- A Pictoral Essay - Ünal, Emre; Arslan, Sevtap; Aghayeva, Gulnar; Sarıkaya, Yasin; Çiftçi, Türkmen; Önder, Sevgen; Akıncı, Devrim; Akhan, Okan (Current Medical Imaging, 2021)
Background: Although imaging findings along with patients’ clinical history may give a clue for the etiology of a pulmonary lesion, the differentiation of benign pulmonary lesions from lung cancer could be challenging. Objective: The aim of this review article was to increase the awareness of carcinoma mimicking lung lesions. Methods: This paper was designed to illustrate rare pulmonary tumors and carcinoma mimickers with emphasis on radiologic-pathologic correlation. Pitfalls encountered on CT images and also false positivity of PET-CT scans were also presented. Conclusion: Several benign pulmonary lesions may grow in size on follow-up and some may show pathologic FDG (18F-fluorodeoxyglucose) uptake, which makes them indistinguishable from lung carcinoma by imaging. In addition, some slow-growing malignant lesions, such as carcinoid, may be false-negative on PET/CT scans.
Keywords: CT